(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Seven varieties of cowpea, Vigna unguiculata L. Walp were studied in two field trials (the wet and dry seasons) in the 2021 cropping season in Agbor, South-South geopolitical zone of Nigeria, were laid out in a complete randomized block design (CRBD) with seven replications for seasonal responses of flowering and pod setting. The dry season crops were manually watered twice daily while the wet season crops were rain-fed. The study recorded that most of the cowpea genotypes grown in the wet season showed photoperiod sensitivity, flowering between 46.36 and 56.43 DAP with mean of 54.97 + 6.98. Pod setting was similar across genotypes but the number (9.64 + 8.29), while length of pods varied (14.66 + 2.83) as noted from field observations. Furthermore, Seeds per pod was not significant among varieties of the wet season but they were significant and among those of the dry season (9.37 + 5.17). Genotypes which flowered earlier produced higher number of pods per plant and gave better yield such as IT06K-149-1, IT98K-128-3, IT95K1072-57 and IT98K-506-1 with grain filling of 205.58, 186.3, 183.53 and 775.99 mean seeds respectively were consequently recommended for hybridization in cowpea breeding programmes in south-south Nigeria.